Republic of Tajikistan : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews Tajikistan's Poverty Reduction Strategy Paper (PRSP) Progress Report. There are positive signs in the initial implementation stages of the Poverty Reduction Strategy process. The revenue performance has improved, and expenditures are managed with tight fiscal discipline. The expenditures in the social sectors were almost 43 percent of the budget in 2003. Cash compensations, increased public sector salaries and increased pensions have targeted social sector spending better. The cash compensations totaled 12 million Sm. in the 2003 budget.